Receptivity and the Thing in Itself: Allison, Allais, and the Problem of Outer Affection in Kant’s Transcendental Idealism - ElMargoushy, Amr (AUC Knowledge Fountain, 2026)
This thesis examines Kant’s distinction between appearances and things in themselves within the framework of transcendental idealism, focusing on how this distinction is meant to secure objective validity while respecting the limits of possible experience. It critically evaluates two influential contemporary interpretations: Henry Allison’s epistemological reading, which understands the distinction as marking different ways of considering the same object, and Lucy Allais’s metaphysical reading, which attributes a grounding role to things in themselves. The thesis argues that while Allison’s reinterpretation successfully avoids noumenal causation by construing affection epistemically, it generates a structural epistemic circularity concerning the role of receptivity and dependence on what is given, whereas Allais’s proposal addresses this difficulty at the cost of reintroducing metaphysical commitments that Kant’s critical project seeks to constrain. The conclusion clarifies the philosophical stakes of this tension and assesses the extent to which Kant’s framework can accommodate receptivity without undermining its epistemic limits.